Toleranţa in "Peccavistanul" lui Salman Rushdie între ruşine şi neruşinare - Cofan, Aluniţa Codruţa (Studia Romanica Posnaniensia, 2003)
After a little theoretical and philosophical introduction to what tolerance means for our contemporary society, we are trying to analyse two ways of the tolerance of the contemporary novelist, Salman Rushdie, in his novel "The Shame". The first of them concerns the discursive tolerance, as a narrative organisation or structure, and the second is about the internal tolerance of the epic ideas. Drawing the conclusions, we can assert the following: for both ways of our examination: the faint and the marginal fight to occupy a central positon belonging to the strong. However, this never wins or if he wins, it is only temporarily. So, even the tolerance has to exist, in fact, it does not exist.